Lepirudin in the management of patients with heparin-induced thrombocytopenia - Sirak Petros (Dove Medical Press, 2008)
Sirak PetrosDepartment of Internal Medicine, University of Leipzig, Leipzig, GermanyAbstract: Lepirudin, a recombinant hirudin, is a direct irreversible thrombin inhibitor by binding to both free and clot-bound thrombin. It is approved for treatment of heparin-induced thrombocytopenia (HIT), which is a serious antibody-mediated drug reaction mostly associated with the use of unfractionated heparin. Clinical experience during the last 10 years has proved the efficacy of lepirudin in the management of HIT. The major route of elimination of lepirudin is the kidney, accounting for approximately 90% of its systemic clearance. The most important adverse reactions are bleeding and the induction of immunologic reactions. The risk of bleeding can be reduced by implementing an optimal monitoring and dose adjustment strategy, particularly in patients undergoing cardiopulmonary bypass surgery and in those with impaired renal function. Development of antihirudin antibodies may enhance the anticoagulant effect of lepirudin. Anaphylactic reactions associated with lepirudin therapy are rare. The lack of an antidote against lepirudin is still a concern, particularly during cardiopulmonary bypass surgery with a heart-lung machine and during artificial renal support. Currently, hemofiltration using high-flux filter systems is the only available and valid means to manage hirudin overdose. Nevertheless, the drug can be safely used if meticulous monitoring strategy is installed.Keywords: lepirudin, hirudin, heparin-induced thrombocytopenia, direct thrombin inhibitors, bleeding